Karma and Causation in Theravāda Buddhism: Rethinking Determinism and External Phenomena - Klairung Iso (Journal of International Buddhist Studies, 2025)
This paper reexamines the relationship between karma and causation in Theravāda Buddhism, with a focus on how karma causes external events attributed to agents. It argues against the deterministic notion that karma directly determines external phenomena, suggesting instead that external phenomena serve as necessary and sufficient conditions for the arising of karmic results. The causal relationship between the arising of contact with external phenomena and the arising of karmic results operates bi-directionally. Narratives that link present experiences to past lives should not be interpreted as implying that the past deterministically causes present events. Rather, they suggest that a moral agent’s feelings arise through present contact with conditions, regardless of the specific external phenomena involved. Drawing from Pāli Sutta-s, Abhidhammattha Sangaha, and Western perspectives on causation, this paper explores both the ontological and epistemological dimensions of karma. It highlights the phenomena of consciousness and emphasizes the roles of cetanā (intention) and vedanā (feeling) as central to the experience and understanding of karma. The study also critiques deterministic interpretations found in popular Thai Buddhism, where karma is often viewed as a fixed explanatory framework for misfortune. Instead, it recommends a naturalistic and experiential approach that emphasizes present awareness and moral responsibility.